Business Strategy Analysis of Kopi Kenangan Using Porter's Five Forces - Ade Agung Gunawan Warja; Abdurahman Abdurahman; Pupung Purnamasari (Jurnal Minfo Polgan, 2024)
This research analyzes the business strategy of Kopi Kenangan using Porter’s Five Forces framework to understand the competitive dynamics in Indonesia’s grab-and-go coffee industry. Utilizing a desk research approach, secondary data from various sources were processed and qualitatively analyzed. The results show that Kopi Kenangan has leveraged brand differentiation, product diversification, and investment support to strengthen its market position. However, threats from new entrants, supplier power, and intense competition remain significant challenges. This study provides strategic insights for coffee industry players to survive and thrive in a competitive market.